Guadalingo: a case study of a gamified video game for learningSpanish as a foreign language - Roxana GAIȚĂ (Revista de Știinţe Educaţiei)
A gamified video game is a game that combines elements of the video game world with educational objectives. In other words, it is an educational tool that applies the elements of the game — like narrative, aesthetics, points, levels, challenges, rewards, missions, characters etc. — to motivate the student and facilitate learning. The reason why I decided to verify the effectiveness of the gamified video game Guadalingo, as a motivating tool in the educational context, is because I am convinced that it adapts to the needs and requirements of new generations of students, as well as the skills required for the 21st century. This study aimed to evaluate the impact of Guadalingo on learning, motivation, overall satisfaction, and as well as in the development of digital skills of the students enrolled at the West University of Timișoara. This quasi-experiment was conducted over 3 academic years, from 2021 to 2024, and both qualitative and quantitative instruments were applied. The results showed a significant improvement in engagement, flow, the feeling of well-being, autonomy, and increased attention span, and support the conclusion that the use of Guadalingo is fun and motivating for students and facilitates Spanish language acquisition.